2022
DOI: 10.1371/journal.pone.0263332
|View full text |Cite
|
Sign up to set email alerts
|

Oral nimodipine treatment has no effect on amyloid pathology or neuritic dystrophy in the 5XFAD mouse model of amyloidosis

Abstract: Dysregulation of calcium homeostasis has been hypothesized to play a role in Alzheimer’s disease (AD) pathogenesis. Increased calcium levels can impair axonal transport, disrupt synaptic transmission, and ultimately lead to cell death. Given the potential role of calcium dyshomeostasis in AD, there is interest in testing the ability of already approved drugs targeting various calcium channels to affect amyloid pathology and other aspects of disease. The objective of this study was to test the effects of FDA-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…S3). We subsequently addressed plaque-associated LAMP1 labeling, a lysosomal marker known to exhibit high expression in plaque-associated DNs [21][22][23][24]. LAMP1 was used to establish whether astroglial plaque coverage was associated with neurite dystrophy.…”
Section: Resultsmentioning
confidence: 99%
“…S3). We subsequently addressed plaque-associated LAMP1 labeling, a lysosomal marker known to exhibit high expression in plaque-associated DNs [21][22][23][24]. LAMP1 was used to establish whether astroglial plaque coverage was associated with neurite dystrophy.…”
Section: Resultsmentioning
confidence: 99%
“…In other matters, CCB highlights promising results in dementia prevention [ 15 , 22 , 23 , 24 ]. Intracellular calcium is elevated in elderly patients and plays a part in neurodegeneration, amyloid production enhancement, and tau hyperphosphorylation [ 15 , 16 , 23 , 46 ]. Thus, CCB may downregulate intracellular calcium levels and slow amyloid production [ 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CCB may downregulate intracellular calcium levels and slow amyloid production [ 16 , 23 ]. In addition, CCB can enhance cerebral vascularization [ 15 ] and, in the case of nimodipine, can act as a cerebral vasodilator [ 46 ]. Among CCB, the dihydropyridine compounds stand out with promising results in Aß42 clearance [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[424] Sadleir et al showed that oral administration of nimodipine to 5XFAD mice did not have a beneficial effect on amyloid pathology, since the molecule did not prevent neuritic dystrophy or reduce cortical or hippocampal Aβ content. [425] However, the treatment did not exacerbate the AD phenotype, suggesting a safety and tolerability profile. It has been described that iron uptake, which competes with Ca 2+ for entry into neurons through the L-type VOCCs, can be inhibited with nimodipine in a dose-dependent fashion in potassium chloride stimulated neuronal cells.…”
Section: Nimodipinementioning
confidence: 91%